2002
DOI: 10.1044/1059-0889(2002/015)
|View full text |Cite
|
Sign up to set email alerts
|

An Auditory Brainstem Implant System

Abstract: Neurofibromastosis type II (NF2) is a condition that may result in bilateral acoustic neuromas. The tumors and their removal may cause profound bilateral deafness. Because the auditory nerve is compromised, people with NF2 are unable to receive a cochlear implant to restore a sensation of hearing. Electrical stimulation of the auditory pathway can provide hearing in such people. This is possible by means of an auditory brainstem implant (ABI). This article focuses on the MED-EL high-rate multichannel ABI syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 2 publications
1
10
0
3
Order By: Relevance
“…The extent of information provided is thought to facilitate lip-reading and the recognition of environmental sounds [9,16,17,18,19,22]. However, significant functional auditory-alone speech recognition is not expected [30,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The extent of information provided is thought to facilitate lip-reading and the recognition of environmental sounds [9,16,17,18,19,22]. However, significant functional auditory-alone speech recognition is not expected [30,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…All patients were implanted using the surgical procedure as described by Matthies et al [16] (2000), Behr et al [18] (2007) and Jackson et al [22] (2002); 6 participants received the MED-EL COMBI 40+ and 26 the ABI. The ABI is a development of the COMBI 40+ offering an electronic platform, which allows a maximum stimulation rate of 50.760 compared to 18.180 pulses/second, which was possible with the COMBI 40+.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional results show great variability; from noise perception only to useful speech discrimination in audiovisual mode in a few patients so far. Since the early trials by Hitselberger and House in 1979, as reported by Edgerton et al 13 and Hit sel berger et al, 21 profound improvements in implant array, technology, and speech processing strategies 65 have brought about useful improvement in functional outcome, 4,8,9,17,23,29,31,32,37,42,43,45,46,48,58,59 but still results remain less favorable than in cochlear implants or auditory brainstem implants (ABIs) in patients without NF2. 8 Visionindependent speech perception is not generally achieved.…”
mentioning
confidence: 99%